Decline in anti-Müllerian hormone concentrations following radioactive iodine treatment in women with differentiated thyroid cancer: A systematic review and meta-analysis. (June 2021) - Anagnostis, Panagiotis; Florou, Panagiota; Bosdou, Julia K.; Grimbizis, Grigorios F.; Iakovou, Ioannis; Kolibianakis, Efstratios M.; Goulis, Dimitrios G.
Highlights: Radioactive iodine (RAI) administration in premenopausal women with differentiated thyroid carcinoma exerts a negative effect on ovarian reserve. Concentrations of anti-Mullerian hormone decrease and remain low at three, six and 12 months compared with baseline. No difference is observed in concentrations of follicle-stimulating hormone (FSH) at six and 12 months after radioactive iodine administration compared with baseline. Abstract: Aim: Radioactive iodine (RAI) is frequently used as adjuvant therapy in patients with differentiated thyroid cancer (DTC). However, its effect on ovarian reserve has not been fully elucidated, with studies yielding inconsistent results. The aim of this study was to systematically review and meta-analyze the best available evidence regarding the effect of RAI on ovarian reserve in premenopausal women with DTC. Methods: A comprehensive literature search was conducted in PubMed, Cochrane and Scopus, through to December 6 th, 2020. Data were expressed as weighted mean difference (WMD) with a 95% confidence interval (CI). The I 2 index was used to assess heterogeneity. Results: Four prospective studies were included in the qualitative and quantitative analysis. Anti-Müllerian hormone (AMH) concentrations decreased at three (WMD -1.66 ng/ml, 95% CI -2.42 to -0.91, p <0.0001; I 2 0%), six (WMD -1.58, 95% CI -2.63 to -0.52, p =0.003; I 2 54.7%) and 12 months (WMD -1.62 ng/ml, 95% CI -2.02 to -1.22, p <0.0001; I 2 15.5%) following a single RAI dose compared with baseline (three studies; n=104). With respect to follicle-stimulating hormone (FSH) concentrations, no difference was observed at six (WMD +3.29 IU/l, 95% CI -1.12 to 7.70, p =0.14; I 2 96.8%) and 12 months (WMD +0.13 IU/l, 95% CI -1.06 to 1.32, p =0.83; I 2 55.2%) post-RAI compared with baseline (two studies; n=83). No data were available for antral follicle count. Conclusions: AMH concentrations are decreased at three months and remain low at 6 and 12 months following RAI treatment in women with DTC. No difference in FSH concentrations post-RAI is observed.